2009
DOI: 10.1111/j.1365-246x.2009.04201.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric seismoelectric Green's function representations

Abstract: S U M M A R YInterferometric Green's function representations can be used to retrieve a Green's function between two receiver stations, effectively turning one receiver into a source. Through reciprocity theorems of the convolution and correlation types, we derive interferometric Green's function representations for coupled electromagnetic and seismic wave propagation in 1-D. These representations express a symmetrized Green's function in terms of correlations of sources distributed throughout the domain of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…We take the principle to the next level by numerically simulating seismoelectric interferometry by cross-correlation. de Ridder et al [46] have already shown, with three numerical examples, that it is indeed possible (under certain conditions) to obtain accurate Green's functions from boundary sources only. Here, we will increase the complexity of the numerical configuration by adding an extra layer to the system, to investigate the Green's function retrieval for a 1D, three-layered system bounded by a free-surface.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…We take the principle to the next level by numerically simulating seismoelectric interferometry by cross-correlation. de Ridder et al [46] have already shown, with three numerical examples, that it is indeed possible (under certain conditions) to obtain accurate Green's functions from boundary sources only. Here, we will increase the complexity of the numerical configuration by adding an extra layer to the system, to investigate the Green's function retrieval for a 1D, three-layered system bounded by a free-surface.…”
Section: Introductionmentioning
confidence: 89%
“…This is not always possible and therefore it is beneficial to be able to replace those strong sources by receivers: the principle of interferometry. In addition, by doing interferometry, stacking inherently takes place with a possible improvement of the signal-to-noise ratio as a result [46]. From an imaging point of view, the principle of interferometry has already been proven useful for a wide class of phenomena, for example in seismic and electromagnetic systems (e.g., Wapenaar et al [47], Slob et al [48]).…”
Section: Introductionmentioning
confidence: 99%
“…Finally we note that focusing of seismic energy could be simulated computationally through techniques like, for example, seismic interferometry (Thorbecke & Wapenaar 2007). This approach can also be used for interferometric Green's function representations of coupled electromagnetic and seismic wave propagation (De Ridder et al 2009). Here we take a different approach and discuss about physical focusing achieved in a medium of known acoustic properties to evaluate the electric properties in its vicinity.…”
Section: Discussionmentioning
confidence: 99%
“…; De Ridder et al . ) and coseismic (Schoemaker et al . ) seismoelectric before being extended by Gao and Hu () to the seismomagnetic aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, seismic interferometry methods using Green's function Wapenaar and Fokkema 2006;Slob and Wapenaar 2007) have been adapted to provide the impulsive seismoelectric response of the porous medium equivalent to the usual transfer functions. This method was first implemented for interfacial (Wapenaar et al 2008;De Ridder et al 2009) and coseismic (Schoemaker et al 2012) seismoelectric before being extended by Gao and Hu (2010) to the seismomagnetic aspects.…”
Section: Introductionmentioning
confidence: 99%